Implementation of Network Planning in the Shophouse Construction Project in Tanjung Morawa District, Deli Serdang Regency - ulfa sururi; cici afrianti; Silvani Nurul Aini Nasution; Ahmad Albar Tanjung (GLOBAL SCIENTS PUBLISHER, 2026)
The construction of shophouses (ruko) as a commercial area requires effective project planning and control to ensure timely completion. This study aims to analyze the application of the Network Planning method in scheduling a shophouse construction project in Tanjung Morawa District, Deli Serdang Regency. The research method used is descriptive quantitative with the Critical Path Method (CPM) and Program Evaluation and Review Technique (PERT) approaches. The research data include the type of work, activity duration, and dependency relationships between activities obtained through field observations, interviews, and project planning documents. Data processing was carried out using the POM for Windows application to determine the earliest start time, latest finish time, slack value, and the project's critical path. The analysis results show that the total project duration is 253 days with the critical path dominated by physical construction activities, especially structural work and the installation of doors and windows. The PERT analysis shows that core construction activities have the highest level of time uncertainty. Thus, the application of Network Planning is proven effective in assisting the planning and time control of shophouse construction projects.